The Short-Term Effect of Caffeine Consumption on Reading Performance - Nazarudin, Alia Natasha; Muhamad, Nurulain; Jufri, Shauqiah (Journal of Health Science and Medical Research, 2024)
Objective: Caffeine, a widely consumed psychoactive substance, is recognized for its cognitive-enhancing effects, notably enhancing performance on tasks requiring narrative comprehension, where it has been shown to boost both acuity and speed. This study investigates the impact of caffeine intake on reading acuity and evaluates changes in reading speed post-caffeine consumption. Material and Methods: Employing a cross-sectional design, nineteen participants with distance best-corrected vision of 6/6 or better (equivalent to logMAR 0.00 or better) (mean age=22.5±1.00 years old) and near vision of 0.1 logMAR (N5) were recruited. Baseline measurements of reading acuity and speed were taken using the article sourced from Perpustakaan Tun Abdul Razak (PTAR) and Buari-Chen Malay Reading Chart (BCMRC) before coffee consumption, respectively. Participants consumed 200 mg of Nescafe Gold (caffeine) before the subsequent assessment. The time taken to read the reading materials was recorded, alongside any errors. Results: While reading speed significantly increased post-caffeine consumption (t=-7.536, p-value<0.001), reading acuity remained unaffected (t=-0.378, p-value=0.705). These results suggest a moderate dose of 200 mg of caffeine can enhance reading speed without compromising acuity in young adults. Conclusion: This indicates that caffeine mainly affects the rate of reading, while it does not alter the reading acuity of individuals.